2017
DOI: 10.3847/1538-4357/aa7edc
|View full text |Cite
|
Sign up to set email alerts
|

Transient Mass-loss Analysis of Solar Observations Using Stellar Methods

Abstract: Low frequency dynamic spectra of radio bursts from nearby stars offer the best chance to directly detect the stellar signature of transient mass loss on low mass stars. Crosley et al. (2016) proposes a multi-wavelength methodology to determine coronal mass ejection parameters, such as Coronal Mass Ejection (CME) speed, mass, and kinetic energy.We test the validity and accuracy of the results derived from the methodology by using Geostationary Operational Environmental Satellite X-ray observations and Bruny Isl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…To estimate the density at 2R * , we assume that density decreases exponentially with height above the base of the corona, following the approach of Crosley et al (2017), who use Sun-as-a-star data to build a framework for interpretation of stellar Type II bursts. We use the density scale height for material in hydrostatic equilibrium (HSE) under constant gravity, H = k B T /(µm H g) ≈ (50 Mm)T 6 R 2 * /M * , where R * and M * are in solar units, and and µ = 0.6 is the mean molecular weight of the solar corona.…”
Section: Choice Of Frequency Bandsmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate the density at 2R * , we assume that density decreases exponentially with height above the base of the corona, following the approach of Crosley et al (2017), who use Sun-as-a-star data to build a framework for interpretation of stellar Type II bursts. We use the density scale height for material in hydrostatic equilibrium (HSE) under constant gravity, H = k B T /(µm H g) ≈ (50 Mm)T 6 R 2 * /M * , where R * and M * are in solar units, and and µ = 0.6 is the mean molecular weight of the solar corona.…”
Section: Choice Of Frequency Bandsmentioning
confidence: 99%
“…Of note are solar Type II and III bursts, which are plasma emission originating from coronal shock fronts and electron beams, respectively. Measuring frequency drift rate, combined with a model of the spatial variation of plasma density or magnetic field strength with height h, enables estimation of an apparent source ve-locity (more detailed treatments can be found in, e.g., Crosley et al 2017). If a source is moving outwards radially at constant speed V = dh/dt, the frequency drift rate ν is:…”
Section: Source Motion Both Plasma Emission and Ecm Canmentioning
confidence: 99%
See 1 more Smart Citation
“…These are now a single variable equations of E rad (v) and v(E rad ). The errors of the above equations are discussed in detail in Crosley et al (2017). The results of equation ( 11) is suggested to be only useful to an approximate order of magnitude while equation ( 12) is suggested to be accurate to within a factor of 2.…”
Section: Flare Observationsmentioning
confidence: 99%
“…Subsequent studies have also found that solar eruptive events tend to have similar amounts of energy in radiation and energetic particles (as measured through X-rays; Emslie et al 2012), while M dwarf flares tend to have a larger fraction of energy in nonthermal particles (Smith, Güdel, & Audard 2005). One positive step forward was recently made by Osten and her collaborators (Crosley, Osten, & Norman 2017), who in effect observed the Sun as an unresolved star in order to develop a framework for the interpretation of stellar events and the derivation of parameters such as CME velocities, masses, and kinetic energies.…”
Section: Extrasolar Space Weathermentioning
confidence: 99%